1975
DOI: 10.1080/03680770.1974.11896071
|View full text |Cite
|
Sign up to set email alerts
|

Plutonium in the Laurentian Great Lakes: food-chain relationships

Abstract: 2^9The radioisotope v Pu, an alpha emitter with a half-life of 24 000 yr, is a small component of fallout from atmospheric weapons testing and at present can be measured in environmental samples by using large samples and performing a rigorous radiochemical separation procedure. The toxicity of plutonium has been of concern since its production was initiated in 1943, with the result that more is known about the toxicology of plutoniurn than about that of most other hazardous elements (Bair and Thompson, 1974).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
1986
1986

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Additional studies of 239,240Pu in Lake Michigan have confirmed the reported concentration range for that lake and shown that the plutonium concentration follows a seasonal cycle in the surface waters while remaining relatively constant in deep waters (2, 3). In addition to the 2:39,240Pu values reported by Wahlgren and Nelson ( I ) , a concurrent study showed that the plankton concentration factor for 239,240Pu from water was the same for all five lakes (4). Alberts et al ( 5 ) have shown that 239,240Pu exists in Lake Michigan waters in a small, anionic form (apparently as a carbonate, bicarbonate, or hydroxide complex).…”
Section: Introductionmentioning
confidence: 87%
“…Additional studies of 239,240Pu in Lake Michigan have confirmed the reported concentration range for that lake and shown that the plutonium concentration follows a seasonal cycle in the surface waters while remaining relatively constant in deep waters (2, 3). In addition to the 2:39,240Pu values reported by Wahlgren and Nelson ( I ) , a concurrent study showed that the plankton concentration factor for 239,240Pu from water was the same for all five lakes (4). Alberts et al ( 5 ) have shown that 239,240Pu exists in Lake Michigan waters in a small, anionic form (apparently as a carbonate, bicarbonate, or hydroxide complex).…”
Section: Introductionmentioning
confidence: 87%
“…Table 12 summarizes some of the reported coefficients. The reported range for algae, inorganic solids and marine sediment (Noshkin, 1972;Hetherington, et al, 1975;Marshall, et al, 1975;Thompson, 1975;Hetherington, 1978; as well as from Nelson, 1976 andEdgington, et al, 1979 is from about 104*5 to lo6 R/kg. Hetherington (1978) showed some dependence of the partition coefficient with particle size and reported values of about Rlkg for particles from 1-10 urn and then a decrease to about for particles from 10 pm to about 70 urn.…”
Section: 3-22mentioning
confidence: 96%